2021
DOI: 10.1177/15347354211045349
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of Glutamine Uptake Improves the Efficacy of Cetuximab on Gastric Cancer

Abstract: Treatment for advanced gastric cancer is challenging. Epidermal growth factor receptor (EGFR) contributes to the proliferation and development of gastric cancer (GC), and its overexpression is associated with unfavorable prognosis in GC. Cetuximab, a monoclonal antibody targeting EGFR, failed to improve the overall survival of gastric cancer patients indicated in phase III randomized trials. Glutamine is a vital nutrient for tumor growth and its metabolism contributes to therapeutic resistance, making glutamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…L-γ-glutamyl-p-nitroanilide (GPNA) suppresses the growth of TNBC, different types of lung cancer, and neuroblastoma cells 73 , 77 , 81 . In addition, combined treatment with GPNA and a monoclonal antibody (cetuximab) targeting EGFR effectively suppressed the growth of gastric cancer cells in vitro and in vivo 86 . However, amino acid analogs are unsuitable for clinical use due to their low affinity, lack of specificity, and toxicity 87 .…”
Section: Targeting Glutamine Transporters As a Treatment For Cancermentioning
confidence: 98%
“…L-γ-glutamyl-p-nitroanilide (GPNA) suppresses the growth of TNBC, different types of lung cancer, and neuroblastoma cells 73 , 77 , 81 . In addition, combined treatment with GPNA and a monoclonal antibody (cetuximab) targeting EGFR effectively suppressed the growth of gastric cancer cells in vitro and in vivo 86 . However, amino acid analogs are unsuitable for clinical use due to their low affinity, lack of specificity, and toxicity 87 .…”
Section: Targeting Glutamine Transporters As a Treatment For Cancermentioning
confidence: 98%
“…In breast cancer, RNF5 loss is associated with increased ASCT2 expression, finally leading to poor patient outcomes, and poor response to paclitaxel ( Jeon et al, 2015 ). ASCT2 is overexpressed on the surface of various tumor cells, such as gastric cancer ( Ma et al, 2021 ), colon cancer ( Ma et al, 2018 ), pancreatic cancer ( Wang et al, 2022 ), and TNBC ( Van Geldermalsen et al, 2016 ). Small molecule inhibitors targeting ASCT2 and other glutamine transporters have been shown to inhibit glutamine uptake and consumption and exhibit antitumor effects in various cancer models.…”
Section: Drugs Targeting Glutamine Metabolism For Cancer Treatmentmentioning
confidence: 99%
“…It is unclear whether the delayed cell growth after GPNA treatment is caused by ASCT2 inhibition. Ma et al demonstrated that blocking ASCT2 with GPNA significantly enhanced the anti-proliferative effect of trastuzumab in gastric cancer in vitro and in vivo ( Ma et al, 2021 ). GPNA treatment also inhibited cell growth in pancreatic cancer ( Wang et al, 2022 ).…”
Section: Drugs Targeting Glutamine Metabolism For Cancer Treatmentmentioning
confidence: 99%
“…Small molecules used to prevent glutamine uptake by inhibiting the primary glutamine transporters, ASCT2, SNAT2, and SNAT1, have suffered from poor affinity, lack of specificity, and toxicity. 10 , 11 , 12 For example, V-9302 was reported as a high-affinity inhibitor of ASCT2, but other studies suggest that it preferentially inhibits SNAT2 and LAT1, the latter being the primary transporter for essential amino acid uptake. 13 , 14 The naturally occurring glutamine analog 6-diazo-5-oxo-L-norleucine (DON) inhibits multiple enzymes that utilize glutamine, including mitochondrial glutaminases, but has translated poorly as a therapeutic primarily due to a narrow therapeutic index leading to gastrointestinal toxicity.…”
Section: Introductionmentioning
confidence: 99%